Entering Into the Story: Implications for Emergent Literacy - Sperry, Linda L.; Sperry, Douglas E. (Frontiers in Psychology, 2021)
In this article we explore the ways in which three young children from a non-mainstream cultural group created stories with the assistance of their caregivers and siblings in the social contexts of their homes. We assert that these children’s oral narrations show us important dimensions of early experience with decontextualized content as practiced in their families that may offer suggestions for analysis of culturally sensitive experiences with literacy for all children. The dimensions we highlight are the tangibility of the elements around which the story is created, the interlocutor support children receive for beginning and continuing their stories, and the interaction between the storytelling process and the child’s self-interest. These three dimensions illustrate how children “enter” into stories and storytelling and broaden our understanding for fostering culturally sustaining pedagogy within schools.